Flexural behavior evaluation of needle-punched glass/jute hybrid mat reinforced polymer composites. (2017) - Zhao, Defang; Mao, Kai; Yang, Yuqiu; Hamada, Hiroyuki
Abstract: In this research, the creation of higher mechanical properties in natural fiber mat composites is proposed. The hybrid jute/glass mat was fabricated by needle-punched system, wherein jute mat was placed on glass mat. The ratio of jute and glass mat layers was set to be 1:0, 1:1, 1:2 and 2:1, respectively. The hand lay-up method was employed to manufacture the composites with unsaturated polyester resin after needle-punched process. Three-point bending test was carried out in order to obtain flexural properties of different composites. The results indicate that flexural strength obtained for jute mat composite (JF) was approximately 37 MPa, whereas high flexural strength was achieved in jute mat/glass mat hybrid composites (JF/GF and JF/JF/GF, when the glass fiber layer is placed as bottom side) that exhibited about respective 61.7 % and 62.0 % higher than the values of JF.